The default mode network and cognition in Parkinson's disease: A multimodal resting‐state network approach - Marina C. Ruppert; Andrea Greuel; Julia Freigang; Masoud Tahmasian; Franziska Maier; Jochen Hammes; Thilo van Eimeren; Lars Timmermann; Marc Tittgemeyer; Alexander Drzezga; Carsten Eggers (2021)
Abstract Involvement of the default mode network (DMN) in cognitive symptoms of Parkinson's disease (PD) has been reported by resting‐state functional MRI (rsfMRI) studies. However, the relation to metabolic measures obtained by [18F]‐fluorodeoxyglucose positron emission tomography (FDG‐PET) is largely unknown. We applied multimodal resting‐state network analysis to clarify the association between intrinsic metabolic and functional connectivity abnormalities within the DMN and their significance for cognitive symptoms in PD. PD patients were classified into normal cognition ( n = 36) and mild cognitive impairment (MCI; n = 12). The DMN was identified by applying an independent component analysis to FDG‐PET and rsfMRI data of a matched subset (16 controls and 16 PD patients) of the total cohort. Besides metabolic activity, metabolic and functional connectivity within the DMN were compared between the patients' groups and healthy controls ( n = 16). Glucose metabolism was significantly reduced in all DMN nodes in both patient groups compared to controls, with the lowest uptake in PD‐MCI ( p < .05). Increased metabolic and functional connectivity along fronto‐parietal connections was identified in PD‐MCI patients compared to controls and unimpaired patients. Functional connectivity negatively correlated with cognitive composite z ‐scores in patients ( r = −.43, p = .005). The current study clarifies the commonalities of metabolic and hemodynamic measures of brain network activity and their individual significance for cognitive symptoms in PD, highlighting the added value of multimodal resting‐state network approaches for identifying prospective biomarkers.